El delito: mera tipicidad y antijuridicidad - Sandoval Molina, César A. (2023)
This article purpo rts to demonstrate that, given the evolution German dogmatic criminal has followed over the previous century, an offense should not be presented as defined, wrongful, and culpable conduct, but rather, simply, as nothing other than definition and wrongfulne ss. In other words, we should return to a bipartite scheme, but following very different standards. With this goal, the author begins by presenting a historical account of the general variants of German criminal dogmatism in constituting an offense. This a rticle does not pretend to examine in depth the theory of offenses, but instead to start from what is already known in order to call attention to the current way of constituting offenses, with the aim of assisting the practice of criminal law in court and the teaching of criminal law.